Applying an IoT Technology in Hydroponic Smart Farming Systems on a Limited Area - Dwi Endah Wahyuni; Marti Widya Sari; Prahenusa Wahyu Ciptadi; R. Hafid Hardyanto; Banu Santoso (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2026)
Population growth continues to drive food demand, while agricultural land becomes increasingly scarce due to urbanization and land conversion. This condition demands agricultural innovations that can increase productivity sustainably in limited land. One emerging solution is the hydroponic system, but managing key parameters such as water temperature, water level, and nutrient content (TDS) is often still done manually, which risks reducing crop quality. This study aims to design and implement an Internet of Things (IoT)-based hydroponic system capable of real-time and remote monitoring. The research method used is an experimental method, including literature review, needs analysis, system design, hardware and software installation, and system testing. The system was developed using an ESP32 microcontroller with a DS18B20 temperature sensor, a JSN SR04T ultrasonic sensor, and a TDS sensor, along with an Android application as the monitoring interface. The design results show that the system can monitor hydroponic conditions in real time, powered by solar panels. This system is expected to improve the efficiency of nutrient management and support the implementation of smart agriculture in limited land.